2009
DOI: 10.4314/sajas.v39i2.44388
|View full text |Cite
|
Sign up to set email alerts
|

Effects of novel feed additives in wheat based diets on performance, carcass and intestinal tract characteristics of quail

Abstract: The present study was conducted to investigate the effects of the supplementation of an antibiotic growth promoter or novel feed additives with or without a xylanase-based enzyme complex to wheat-based diets on the growth performance, carcass yields and quality and intestinal characteristics (length of the total and small intestine, pH and viscosity of digesta, microflora) of Japanese quail. Eight hundred and forty day-old male quail chicks were randomly assigned to 14 groups of similar mean weight each of whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
1
9

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 45 publications
(45 reference statements)
4
22
1
9
Order By: Relevance
“…This result obtained from our study confirmed the previous results: under normal practical conditions, the beneficial effects of dietary supplementation of microbial feed additives (probiotics/eubiotics) in several poultry species were not regulated by any changes in voluntary FI (Gao et al, 2008;Sarica et al, 2009), but they have a significant effect on the alleviation of reduced FI and depressed birds' performance under subclinical infections (Kulshreshtha et al, 2017;Jiang et al, 2010). Therefore, the enhanced laying performance by the eubiotic mixture 1 supplementation in our trial was not obtained by the regulation of FI of the hens, but it could rather be due to their probiotic/eubiotic effects at the sites of digestion and absorptions improving digestibility and uptake of nutrients.…”
Section: Experiments With Eubiotic Mixturesupporting
confidence: 82%
See 1 more Smart Citation
“…This result obtained from our study confirmed the previous results: under normal practical conditions, the beneficial effects of dietary supplementation of microbial feed additives (probiotics/eubiotics) in several poultry species were not regulated by any changes in voluntary FI (Gao et al, 2008;Sarica et al, 2009), but they have a significant effect on the alleviation of reduced FI and depressed birds' performance under subclinical infections (Kulshreshtha et al, 2017;Jiang et al, 2010). Therefore, the enhanced laying performance by the eubiotic mixture 1 supplementation in our trial was not obtained by the regulation of FI of the hens, but it could rather be due to their probiotic/eubiotic effects at the sites of digestion and absorptions improving digestibility and uptake of nutrients.…”
Section: Experiments With Eubiotic Mixturesupporting
confidence: 82%
“…This improvement did not associated with any increase in feed intake (FI) of the broiler chickens in this experiment. In generally, the monogastric animals did not increase their FI with the diets supplemented with probiotic, prebiotics and essential plant oils (Fallah, 2016;Gao et al, 2008;Sarica et al, 2009). Supplementing the diets with 0.5 and 1.0% of eubiotic mixture 1 at commercial condition is highly recommended to enhance the growth rate.…”
Section: Experiments With Eubiotic Mixturementioning
confidence: 99%
“…It was 72.2% in younger birds and 72.5% in older birds. In another study (Sarica et al, 2009), which evaluated the effect of new feed additives (e.g. flavomycin, probiotic and prebiotic) on carcass quality, carcass yield and intestinal characteristics of 35-day-old male Japanese quail showed a higher percentage of small intestine (91.2%) than in our study.…”
Section: Resultsmentioning
confidence: 81%
“…Japanese quail are significantly more often used as experimental animals in scientific research. It was found that the weight, body conformation, and morphometry of internal organs of quail are influenced by many factors such as birds' age (Yalcin et al, 1995;Mihailov, 2006;Mihailov et al, 2008) and sex (Shata, 2001), type and composition of feed (Tarasewicz et al, 2007), type of feed additives (Aydin et al, 2004;Sarica et al, 2009;Bonos et al, 2010;Teshfam et al, 2011), rearing methods (Kul et al, 2006), stocking density (Abdel-Azeem, 2010) and ambient temperature (Özbey et al, 2004). Mihailov et al (2008) observed that the digestive tract of Japanese quail becomes morphologically and functionally mature between 7 and 14 days of age, after which the linear changes in the digestive tract are less significant.…”
Section: Introductionmentioning
confidence: 99%
“…Sarica et al (14) did not observe differences in quail growth performance when quails were fed wheat-based diets and enzymes. Langhout and Schutte (15) reported that wheat-based diets and enzyme supplementation did not bring changes in broiler chickens feed intake.…”
Section: Performancementioning
confidence: 99%